Validity of value-based consumer behaviour models in terms of the financial awareness of Generations Z and Y - Garai-Fodor, Mónika; Csiszárik-Kocsir, Ágnes (Public Finance Quarterly, 2023)
The purpose of our research was to investigate whether theories on value-based consumer behaviour – i.e. the correlation between individual value orientation and specific consumer choices – are also relevant with regard to money-related decisions. 91 percent of our sample of 3,736 people belonged to Generations Y and Z (a ratio of 17:74). Based on the results obtained, it can be stated that the values and mindset of the selected generations exhibit differences compared to previous generations, and because of their malleable value judgements, their purchase and consumer choices, including financial decisions, can be influenced by appropriate means. In the primary study, we analysed the value orientation of young people in relation to money and found that they considered the sense of security provided by money and its long-term value dimension as the most important aspects. We have also examined how young people manage money and how their financial decisions are taken. In this respect, we established that the most characteristic features were price-awareness and information collection before making financial decisions, which demonstrated the strength of the cognitive part of the attitude. As a result of the research, based on the perceptions of the value of money, four consumer groups could be characterised among young people, while based on money management, seven consumer groups. The analysis of the relationship between individual consumer segments confirmed that there is a correlation between the perception of the value of money and the way in which financial decisions are made. When characterising the individual segments, it became clear in which groups financial knowledge needs to be improved, and the members of which groups may serve as reference people and opinion leaders in the promotion of conscious spending.